The effect of corporate social responsibility philanthropic programs towards employee job satisfaction: a case study on Awana Genting Golf and Country Resort / Norhaslinda Jamaluddin and Nik Azreeta Nik Aziz - Jamaluddin, Norhaslinda; Nik Aziz, Nik Azreeta (Faculty of Hotel & Tourism Management, 2013)
Corporate social responsibility (CSR) program is becoming one of major trends in business world due to its significance towards organization’s financial performance. It has been proven that CSR also have a direct link to the employees but there are very few studies focused on employee engagement in CSR and employee job satisfaction. This study is conducted to identify the components of CSR philanthropic program that mostly practiced by the organization, to examine employee engagement in CSR philanthropic programs and to examine level of employee job satisfaction in CSR philanthropic programs. This study use descriptive approach which focusing on employees of Awana Genting Golf and Country Resort. Data is gathered from primary data by distributing questionnaire to 335 employees and 185 questionnaires have been collected. The questionnaire was distributed to the employees of selected department such as food and beverage, housekeeping, finance, front office, human resource, golf course and security department. Standard multiple regressions is used in this study and to ensure that the data obtained met the purpose of the study. It was found that there is a significant relationship between CSR philanthropic, employee engagement and employee job satisfaction as well as employee engagement mediates CSR philanthropic and job satisfaction. The implication of the study is discussed in which it will help the organization to improve their organizational performance.